Engineering management : - Chang, C.M. (Pearson, 2005)
For senior and first-year graduate courses in technology and engineering including aerospace, biomedical, chemical, computer, electrical, mechanical, industrial, and systems engineering. This easy-to read-text covers a wide range of relevant topics affecting the future roles of engineering managers, contains over 80 examples and 120 chapter-end questions, articulates a forward-looking globally orientated perspective, and emphasizes a six-dimensional challenge for engineers in the new millennium. The book is organized in three parts: Part I reviews the basic functions of engineering management; Part II provides backgrounds in cost accounting, financial analysis, financial management and marketing management; and Part III readies the student for exercising leadership in managing technologies through discussions related to engineers as managers/leaders, ethics, web-based tools, globalization and engineering management in the decades to come.